Criminal Defense Investigation – instrument to improve the evidence debate in the criminal procedure - Franklyn Roger Alves Silva (Revista Brasileira de Direito Processual Penal)
The present article examines criminal defense investigation in Brazilian legal system as an instrument necessary to improve the production of evidence in the criminal procedure. Although there are not rules about defense search for evidence, the study demonstrates the potential for Brazilian criminal procedure law based on Italian and North American experience, as well as the recent standard edited by the Brazilian Bar Association.